2016
DOI: 10.2147/copd.s118415
|View full text |Cite
|
Sign up to set email alerts
|

Computer quantification of “angle of collapse” on maximum expiratory flow volume curve for diagnosing asthma-COPD overlap syndrome

Abstract: BackgroundIn a previous study, we demonstrated that asthma patients with signs of emphysema on quantitative computed tomography (CT) fulfill the diagnosis of asthma-COPD overlap syndrome (ACOS). However, quantitative CT measurements of emphysema are not routinely available for patients with chronic airway disease, which limits their application. Spirometry was a widely used examination tool in clinical settings and shows emphysema as a sharp angle in the maximum expiratory flow volume (MEFV) curve, called the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…In addition, computer quantification of AC on MEFV curve has been proved to be an alternative method for predicting the presence of emphysema, which consequently facilitates the emphysema-predominant COPD phenotype determination. 26 28 In this study, we categorized COPD into emphysema-predominant phenotype and nonemphysema-predominant phenotype according to the computer quantification of AC. Our results were obtained on disease heterogeneity perspective, which showed that COPD, especially the emphysema-predominant phenotype was significantly associated with worsened OS of squamous carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, computer quantification of AC on MEFV curve has been proved to be an alternative method for predicting the presence of emphysema, which consequently facilitates the emphysema-predominant COPD phenotype determination. 26 28 In this study, we categorized COPD into emphysema-predominant phenotype and nonemphysema-predominant phenotype according to the computer quantification of AC. Our results were obtained on disease heterogeneity perspective, which showed that COPD, especially the emphysema-predominant phenotype was significantly associated with worsened OS of squamous carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“… 26 , 27 We referred to the Topalovic’s method to make a quantitative measurement of AC. 27 According to our previous research, 28 the raw PFT data points of the MEFV curve were reestablished and analyzed by a computer model. The ACs were measured with standard procedures using the computer model based on Matlab software 8.5 (The MathWorks, Natick, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, computer quantification of AC on the MEFV curve was used to categorize phenotypes: emphysema-predominant and non-emphysema-predominant. 35 37 The results obtained showed that compared to non-COPD, both phenotypes independently increased the risk of overall lung cancer and most lung cancer subtypes (including adenocarcinoma, SCC, SCLC, and large-cell carcinoma). A previous cross-sectional study reported that the risk odds of SCC were significantly increased among lung cancer patients with emphysema.…”
Section: Discussionmentioning
confidence: 98%
“…The procedure was performed according to previous work. 37 A few COPD patients whose raw PFT data were not available were excluded from further analysis. Studies have demonstrated that sharp AC in the MEFV curve is an indicator of emphysema.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation